A Study of PP/Natural Fiber Composites Using Thermoplastic Lignin-polyester and Nanoclay - Park, In-Kyung; Hau, Neo Chun; Kim, Young Jun; Yun, Ju-Ho; Kim, Soo Hyun; Suhr, Jonghwan; Lee, Young-Kwan; Nam, Jae-Do (한국고분자학회, 2016)
Lignin has derived from black liquor or wood, and it shows a lack of thermal stability, which restricts its direct use in industrial applicaion. Synthesized lignin polyester (LigPS) from lignin can be melt-processable and matrix of composites. We investigated the jute-fiber/polypropylene (PP) composite system by incorporating LigPS and montmorillonite (MMT) nanoplatelets through extrusion and injection molding processes. The modulus of PP/jute/LigPS composite was increased due to its compatibilizing effect in the PP-jute interface. Also the water resistance was increased, when LigPS was incorporated into PP/jute composites in 5 wt%. While the montmorillonite nanoclay was added and exfoliated in the PP/jute composites by 5 wt%, the modulus was substantially increased by 50%. As a novel green composite system, the LigPS and MMT nanoplatelets demonstrated that the compatibility, the water resistance and the mechanical performance of PP/jute composites could be desirably tailored for various eco-friendly composite applications.